Enhancing Professional Development of English-Medium-Instruction Business Content Teacher in China's Higher Education: Developing Tailored Training Frameworks. - Shen, Yu (UMA Editorial, 2025)
This dissertation investigates the emerging professional group of English-Medium Instruction Business Content Teachers (EMIBCTs) in Chinese higher education, addressing their dual competency requirements in business knowledge and English proficiency. Distinct from traditional English for Specific Purposes (ESP) teachers, EMIBCTs face unique challenges in integrating specialised business content with English instruction. The research employs Needs Analysis Theory, Lifelong Learning Theory, and Teacher Professional Development Theory to explore their training needs, professional identity, and instructional practices. Using a mixed-methods approach, the study includes surveys of 228 teachers and 185 training participants, along with in-depth interviews with eight representative teachers. EMIBCTs are categorised into four groups based on their English proficiency and business expertise. Findings reveal gaps in EMI methodologies, bilingual instruction, and ELF awareness, with national policies often mandating immersive English teaching but providing limited explicit pedagogical guidance. The study highlights that many EMIBCTs perceive themselves as language instructors rather than business content experts, indicating a need for systematic training and professional development. A differentiated training framework is proposed, emphasising conceptual knowledge (ELF awareness, CLIL principles), skill-based knowledge (language enhancement, translanguaging), and professional development (career exploration, collaborative platforms). These findings provide actionable insights for policymakers, curriculum designers, and individual teachers to enhance EMI implementation. The research contributes to the internationalisation of Chinese higher education and addresses global challenges of non-native English-speaking educators delivering content in English.
Keywords: Inglés - Estudio y enseñanza - Estudiantes extranjeros; Profesores de inglés; Profesores - Formación profesional - Tesis doctorales; English-Medium-Instruction; ELF awareness; Teacher Identity